India : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that India's economy has continued to grow above trend, with an average growth of 8 percent in the last three years. Growth is broad based, with robust consumption, investment, and exports. With manufacturing expanding at more than 10 percent y/y, industry has joined services as an engine of growth. Net foreign investor inflows rebounded after the May/June 2006 stock market correction, and stock prices recovered smartly, reaching new historical highs. Real estate prices continue to grow at a rapid clip on the back of a credit boom.